Research on Cumulative Deformation Characteristics of Subgrade Filling under Cyclic Train Loading. (8th April 2022) - Yao, Junkai; Ye, Yangsheng; Cai, Degou; Bi, Zongqi; Yan, Hongye
Abstract : The smoothness of high-speed railway is extremely strict. As an important part of the high-speed railway foundation, the subgrade structure has strict deformation requirements. It is necessary to ensure that the subgrade structure does not have plastic cumulative deformation under the long-term cyclic load of the train, which is the most critical geodynamic problem in high-speed railway subgrade. This paper studied the cumulative deformation characteristics of subgrade filling under cyclic train loading through the cyclic triaxial test, three types of accumulative plastic deformation trends, and the value of critical volume shear strain was discussed, which would provide the theoretical support for the dynamic design of high-speed railway.